A benefits dependency network as the bridge between requirements and business objectives: an ODE perspective. (12th July 2011) - King, Nelson
The chasm between information system requirements and business objectives is a leading cause of failure. Requirements are often established without understanding the implications to workflow and organisational change. While stakeholder analysis provides useful insights for the 'big picture', the impact of requirements on stakeholder interests aren't known. Similarly, low-level process modelling has trouble representing the broader organisational design and business objectives. The benefits dependency network (BDN) serves as a bridge between the two by tracing the impact of key technical requirements on organisational change, resultant outcomes, and benefits that accrue to stakeholders. Ambulatory e-prescribing in the USA serves as the case for illustrating a BDN analysis. The case is built using interpretive description that synthesises hundreds of related studies in healthcare to capture the breadth and depth of the e-prescribing context. The paper suggests BDN has utility as an integrative framework for understanding the inter-twined contributions of organisational design and artefact engineering upon various stakeholders.